Dealing with abiotic stresses: an integrative view of how phytohormones control abiotic stress-induced oxidative stress - Souza, Lucas A.; Monteiro, Carolina C. [UNESP]; Carvalho, Rogério F. [UNESP]; Gratão, Priscila L. [UNESP]; Azevedo, Ricardo A. (Springer Nature, 2017)
There is a very effective cross-talk between signals triggered by reactive oxygen species and the hormonal response in plants, inducing the expression of genes or activating proteins/enzymes likely to be involved in stress tolerance. Although abiotic stress responses and the role of the antioxidant system have been well explored in the literature, the understanding of the interrelationship between hormones and their effects on antioxidant system is not clear or well investigated. We attempted to scan the field of hormonal modulation of oxidative stress in plants. We feel that this topic is one of the most promising and emerging field in abiotic stress research because multiple responses can be controlled by hormones. We are presenting an overview of the more recent literature on what has been done regarding the interaction between auxin (AUX), gibberellins (GA), cytokinins (CK), abscisic acid (ABA), ethylene (ET) and oxidative molecules and antioxidant compounds. Even knowing that several stress-responsive genes respond to hormones, some of which have already been documented showing that AUX, GA, CK, ABA and ET are part of stress signaling, a lot more is needed in order to have a clearer view of how and which hormones regulate abiotic stress responses.
Keywords: Abiotic stress; Antioxidant system; Hormones; Plant signaling; Reactive oxygen species